Corrosion inhibition by henna leaves extract in industrial wastewater - Nur Afrina, Kamarul Bahrin (2019)
A corrosion inhibitor is a chemical compound which added to industrial wastewater in order to reduce the rate of corrosion. It can slows the attack of acid corrosion towards tubing, drill pipe and any other metals that contact with acid during treatment. However, the cost of using corrosion inhibitor is expensive. Therefore, the solution of this problem is by using plant extract as corrosion inhibitor. This study aims to determine the optimum dosage of inhibitor on mild steel in 1M HCl and the effect of temperature and contact time on mild steel in 1M HCl. Corrosion inhibition effect of Henna Leaves Extract (Lawsonia inermis) on mild steel in 1 M HCl has been investigated by weight loss method. Experiments will be conducted at 25℃, 40℃, 50℃, 60℃, and at room temperature with different concentration of henna leaves extract. The immersion time is 4 weeks to calculate the inhibition efficiency. The highest efficiency is 6% which is at the concentration of henna leaves is 35g/L. For rate of corrosion, the reading is unfactured where at 5g/L of concentration, the rate of corrosion is decreased. The optimum dosage of henna leaves extract for efficiency of inhibitor was 35g/L. As for the effect of temperature, when the temperature was increased, the inhibition efficiency also increased. It can be compared that when the concentration of inhibitor is 35g/L, the inhibition efficiency was lower (1.84%) at 25℃ compared to the temperature at 60℃ which is 6.29%. For the contact time, it have the highest inhibition efficiency reading at the fourth week. When at the fourth week, the inhibition efficiency is 6.29% while at the first week, the inhibition efficiency is 4.08%. For the adsorption isotherms, the Langmuir graph shows that the adsorption of henna leaves extract (Lawsonia inermis) obeys Langmuir adsorption isotherm. As a conclusion, Henna leaves can be used in reduce the corrosion of equipments in industrial wastewater. It also has the tendency to be a good inhibitor. By using henna leaves, it can control and reduce the corrosion where it can reduce the cost.